2019
DOI: 10.1017/ice.2019.352
|View full text |Cite
|
Sign up to set email alerts
|

Association between statewide adoption of the CDC’s Core Elements of Hospital Antimicrobial Stewardship Programs and rates of methicillin-resistant Staphylococcus aureus bacteremia and Clostridioides difficile infection in the United States

Abstract: Objective:To measure the association between statewide adoption of the Centers for Disease Control and Prevention’s (CDC’s) Core Elements for Hospital Antimicrobial Stewardship Programs (Core Elements) and hospital-associated methicillin-resistant Staphylococcus aureus bacteremia (MRSA) and Clostridioides difficile infection (CDI) rates in the United States. We hypothesized that states with a higher percentage of reported compliance with the Core Elements have significantly lower MRSA and CDI rates.Participant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 26 publications
0
4
0
Order By: Relevance
“…Although prevention of C difficile has generally focused on interventions targeting symptomatic patients in healthcare settings, such as isolation and environmental cleaning, increasing data suggest that symptomatic healthcare cases are not the only source for transmission [ 7 ]. Thus, interventions focused on symptomatic patients, although important and effective, will need augmentation from additional measures [ 8 ]. The variation in the proportion of cases that are community acquired, as well as differences in the likelihood that patients are symptomatic, suggest that interventions in the community and long-term care settings are both likely needed to aid transmission reduction [ 7 , 9 , 10 ].…”
Section: Discussionmentioning
confidence: 99%
“…Although prevention of C difficile has generally focused on interventions targeting symptomatic patients in healthcare settings, such as isolation and environmental cleaning, increasing data suggest that symptomatic healthcare cases are not the only source for transmission [ 7 ]. Thus, interventions focused on symptomatic patients, although important and effective, will need augmentation from additional measures [ 8 ]. The variation in the proportion of cases that are community acquired, as well as differences in the likelihood that patients are symptomatic, suggest that interventions in the community and long-term care settings are both likely needed to aid transmission reduction [ 7 , 9 , 10 ].…”
Section: Discussionmentioning
confidence: 99%
“…According to a 2018 survey, 85% of acute care hospitals in the United States had seven core elements, an increase from 41% in 2014 [ 99 ]. A study in the United States revealed that a 1% increase in the proportion of hospitals performing core elements was associated with a 0.3% lower incidence of hospital-acquired CDI [ 131 ]. In this study, the performance of the core elements and MRSA showed no significant correlation [ 131 ].…”
Section: Asp Activation Plan In Korean Medical Facilitiesmentioning
confidence: 99%
“…A study in the United States revealed that a 1% increase in the proportion of hospitals performing core elements was associated with a 0.3% lower incidence of hospital-acquired CDI [ 131 ]. In this study, the performance of the core elements and MRSA showed no significant correlation [ 131 ]. The advantages of meeting the core elements include reducing the use of antimicrobials for acute upper respiratory tract infections in outpatients and improving the appropriateness of use and cost-effectiveness [ 132 ].…”
Section: Asp Activation Plan In Korean Medical Facilitiesmentioning
confidence: 99%
“…Treatment failure increases medical costs and hospital stays, and Clostridioides difficile infection resulting from the misuse of antibiotics. Irrational prescribing can be result of a lack of drug understanding, unethical drug promotion, a high patient load, inefficient laboratory facilities, medication availability, ineffective law enforcement, and failure to assure compliance with recommendations [2,3].…”
Section: Introductionmentioning
confidence: 99%